2017
DOI: 10.1002/ags3.12002
|View full text |Cite
|
Sign up to set email alerts
|

Does postoperative morbidity worsen the oncological outcome after radical surgery for gastrointestinal cancers? A systematic review of the literature

Abstract: PurposeThe impact of postoperative complications on survival after radical surgery for esophageal, gastric, and colorectal cancers remains controversial. We conducted a systematic review of recent publications to examine the effect of postoperative complications on oncological outcome.MethodsA literature search of PubMed/MEDLINE was performed using the keywords “esophageal cancer,” “gastric cancer,” and “colorectal cancer,” obtaining 27 reports published online up until the end of April 2016. Articles focusing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 92 publications
3
59
0
Order By: Relevance
“…The adverse effect of complications after cancer surgery on survival has been reported in several solid malignancies, including colorectal and head and neck cancer as well as gastric cancer . For example, Tokunaga et al analyzed 765 patients and found that grade 2 or higher intra‐abdominal infectious complications after radical resection of gastric cancer adversely affect survival .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The adverse effect of complications after cancer surgery on survival has been reported in several solid malignancies, including colorectal and head and neck cancer as well as gastric cancer . For example, Tokunaga et al analyzed 765 patients and found that grade 2 or higher intra‐abdominal infectious complications after radical resection of gastric cancer adversely affect survival .…”
Section: Discussionmentioning
confidence: 99%
“…The adverse effect of complications after cancer surgery on survival has been reported in several solid malignancies, including colorectal and head and neck cancer as well as gastric cancer. 7,[17][18][19] For example, Tokunaga et al analyzed 765 patients and found that grade 2 or higher intra-abdominal infectious complications after radical resection of gastric cancer adversely affect survival. 5 A propensity score matching was conducted by Fujiya et al to assess the prognostic F I G U R E 3 Significance of the association of postoperative complications with recurrence-free survival impact of postoperative intra-abdominal infectious complications graded 2 or higher, and they found that overall (HR 1.43) and recurrence-free survival (HR 1.42) survival were significantly shortened in patients with complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previous studies reported, fewer postoperative complications might contribute to a better prognosis. 11,12 Although the number of harvested lymph nodes in D3 with LCA preservation was lower than that in D3 without LCA preservation, we considered it sufficient to dissect D3 lymph nodes oncologically through D3 with LCA preservation because the present study revealed the non-inferiority of D3 with LCA preservation in terms of prognosis compared with D3 dissection without LCA preservation. Although it is unknown whether the D3 lymph node dissection is necessary or not, JSCCR guideline recommends the D3 lymph node dissection.…”
Section: Discussionmentioning
confidence: 74%